Short-term isothermic heat acclimation elicits beneficial adaptations but medium-term elicits a more complete adaptation - Moss, J. N.; Bayne, F. M.; Castelli, F,; Naughton, M. R.; Reeve, T. C.; Trangmar, S. J.; Mackenzie, R. W. A.; Tyler, C. J. (European Journal of Applied Physiology, 2020)
Purpose: To investigate the effects of 60 min daily, short-term (STHA) and medium-term (MTHA) isothermic heat acclimation (HA) on the physiological and perceptual responses to exercise heat stress. Methods: Sixteen, ultra-endurance runners (female = 3) visited the laboratory on 13 occasions. A 45 min sub-maximal (40% Wmax) cycling heat stress test (HST) was completed in the heat (40 °C, 50% relative humidity) on the first (HSTPRE), seventh (HSTSTHA) and thirteenth (HSTMTHA) visit. Participants completed 5 consecutive days of a 60 min isothermic HA protocol (target Tre 38.5 °C) between HSTPRE and HSTSTHA and 5 more between HSTSTHA and HSTMTHA. Heart rate (HR), rectal (Tre), skin (Tsk) and mean body temperature (Tbody), perceived exertion (RPE), thermal comfort (TC) and sensation (TS) were recorded every 5 min. During HSTs, cortisol was measured pre and post and expired air was collected at 15, 30 and 45 min. Results: At rest, Tre and Tbody were lower in HSTSTHA and HSTMTHA compared to HSTPRE, but resting HR was not different between trials. Mean exercising Tre, Tsk, Tbody, and HR were lower in both HSTSTHA and HSTMTHA compared to HSTPRE. There were no differences between HSTSTHA and HSTMTHA. Perceptual measurements were lowered by HA and further reduced during HSTMTHA. Conclusion: A 60 min a day isothermic STHA was successful at reducing physiological and perceptual strain experienced when exercising in the heat; however, MTHA offered a more complete adaptation.